Determinants of Tea Production in Indonesia, 1990–2023: An Error Correction Model (ECM) Approach - Ciomai Ciomai; Dian Hafizah; Nofialdi Nofialdi; Arni Lusi (Darul Yasin Al Sys, 2026)
Indonesian tea production showed a declining and fluctuating trend during 1990–2023, while studies that simultaneously examine the effects of plantation area, tea prices, and tea exports on production in both the short and long run remain limited. This study aims to analyse the effects of plantation area, tea prices, and tea exports on Indonesian tea production. A quantitative approach with a time-series design was employed using 34 annual observations covering the study period. Secondary data were obtained from BPS-Statistics Indonesia, the Food and Agriculture Organization, the World Bank, and other official sources. The data were analysed using the Error Correction Model through stationarity testing, cointegration testing, multicollinearity assessment, and long- and short-run estimations. The results show that all variables were integrated at first difference and cointegrated in the long run. Plantation area, tea prices, and tea exports had positive and significant effects on tea production in the long run, whereas only tea exports had a significant effect in the short run. The negative and significant Error Correction Term indicates a rapid adjustment toward long-run equilibrium. These findings contribute to plantation economics by clarifying the temporal dynamics of production determinants in Indonesia’s tea sector. The study implies that land optimisation, stronger price incentives, and improved export competitiveness are essential to strengthening tea production performance and supporting the sustainability of the national plantation industry.